How does ocean farming empower the fishery economy? A policy impact evaluation of marine ranch demonstration zones - Wu, Zhengjie; Ma, Jintao; Zhou, Yufei; Hu, Qiuguang (Frontiers in Marine Science, 2025)
IntroductionThe construction of marine ranches, as a crucial component of implementing the "Big Food Concept" and the "Strengthening the Ocean" strategy, provides new solutions for the sustainable development of marine resources and the growth of the fishery economy.MethodsThis study centers on investigating the impact mechanisms of marine ranch demonstration zones on fishery output value, employing a multi-period difference-in-differences (DID) model with panel data from 43 coastal prefecture-level and above cities in China from 2007 to 2022 to empirically evaluate policy effects at municipal level.ResultsKey findings reveal that marine ranch demonstration zone construction significantly drives fishery output growth by improving marine ecosystems, extending industrial chains, and conserving biological resources, thereby enhancing fisheries' stability and sustainability while upgrading economic quality and efficiency; policy effects exhibit spatial and typological heterogeneity, with enhancement-oriented and recreation-oriented marine ranches demonstrating more pronounced impacts, while cities in the East and South China Sea regions capitalize more effectively on the economic benefits.DiscussionThese findings position marine ranch as a critical pathway transforming ecological benefits into economic gains. We propose accelerating sustainable "blue granary" development through three strategic priorities: refining modern marine ranch policy frameworks, implementing regionally differentiated strategies, and fostering diversified synergistic development approaches.